2005
DOI: 10.1103/physrevlett.95.267207
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Ultrafast Magnetization Dynamics

Abstract: We present a microscopic model that successfully explains the ultrafast equilibration of magnetic order in ferromagnetic metals at a time scale tau(M) of only a few hundred femtoseconds after pulsed laser excitation. It is found that tau(M) can be directly related to the so-called Gilbert damping factor sigma that describes damping of GHz precessional motion of the magnetization vector. Independent of the spin-scattering mechanism, an appealingly simple equation relating the two key parameters via the Curie te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
378
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 445 publications
(397 citation statements)
references
References 20 publications
18
378
0
1
Order By: Relevance
“…The initial relaxation time scale in the ultrafast regime is τ i ∼ (α * h−1 k B T eff ) −1 . This generalizes the result of Koopmans et al [7] for the ultrafast relaxation of the longitudinal magnetization to arbitrary α * based on the transverse spin diffusion [20]. The notion of magnons becomes questionable when the intrinsic linewidth approaches the magnon energy, which corresponds to α * ∼ 1.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The initial relaxation time scale in the ultrafast regime is τ i ∼ (α * h−1 k B T eff ) −1 . This generalizes the result of Koopmans et al [7] for the ultrafast relaxation of the longitudinal magnetization to arbitrary α * based on the transverse spin diffusion [20]. The notion of magnons becomes questionable when the intrinsic linewidth approaches the magnon energy, which corresponds to α * ∼ 1.…”
supporting
confidence: 83%
“…Despite their different appearances, the microwave, thermal, and ultrafast spin dynamics are all rooted in the exchange interactions between electrons. It is thus natural to try to advance a microscopic understanding of the ultrafast spin dynamics based on the established phenomena at lower energies.Although some attempts have been made [7,8] to extend the LLG phenomenology to describe ultrafast demagnetization in bulk ferromagnets, no firm connection exists between the ultrafast spin generation at interfaces and the microwave spin-transfer and spin-pumping effects [9] or the thermal spin Seebeck and Peltier effects. In this Letter, we unify the energy regimes of microwave, thermal, and ultrafast spin dynamics in magnetic heterostructures from a common microscopic point of view.…”
mentioning
confidence: 99%
“…9 In the model, possible "nonthermal" contributions to the demagnetization, like angular momentum transfer from laser photons or enhanced spin-flip scattering during pump-probe overlap, are disregarded since the total number of photons involved in the process is estimated to be too small to give rise to sizable effects. 4 Using a complementary approach, Zhang and Hübner ͑ZH͒ attempted to explain the demagnetization process as the result of the combined action of spin orbit coupling ͑SOC͒ and the interaction between spins and laser photons.…”
Section: Influence Of Photon Angular Momentum On Ultrafast Demagnetizmentioning
confidence: 99%
“…Pioneering experiments [24] on ferromagnetic thin films revealed that the magnetization experiences a rapid drop (on a femtosecond time scale) when the films is irradiated with an ultrafast laser pulse, after which it slowly regains its original value on a time scale close to that of the electron-phonon coupling. Despite many attempts [24,25,26], a clear theoretical explanation for these effects is still lacking. Here, we will illustrate how this problem can be addressed using some of the techniques developed for the electron dynamics, particularly quantum mean-field and phase-space methods, which will be generalized to include the spin degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%